Pendampingan Suami pada Kunjungan ANC (Antenatal Care) berhubungan dengan Tingkat Kecemasan Ibu Hamil Trimester III - Sri Hardiani; Humaediah Lestari; Linda Lestari; Haryani Haryani (LPPM STIKES Mataram, 2024)
Abstarct Introduction: husbands are expected to be involved in decision making and taking action regarding maternal health, including providing a sense of security and reducing anxiety for pregnant women with the husband's assistance. The third trimester of pregnancy is the final age of pregnancy and before delivery. Pregnancy in the third trimester is often referred to as the vigilant